A Modified Advanced Encryption Standard Algorithm for Image Encryption - Tahir, Ari Shawkat (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Cryptography algorithms are becoming more necessary to ensure secure data transmission, which can be used in several applications. Increasing use of images in industrial process therefore it is essential to protect the confidential image data from unauthorized access. Advanced Encryption Standard (AES) is a well- known block cipher that has many benefits in data encryption process.Â  In this paper, proposed some modification to the Advanced Encryption Standard (M-AES) to increase and reaching high level security and enhance image encryption. The modification is done by modifying the ShiftRow Transformation. Detailed results in terms of security analysis and implementation are given. Comparing the proposed algorithm with the original AES encryption algorithm shows that the proposed M-AES has more security from the cryptographic view and gives better result of security against statistical attack.